(untitled) (Journal of Hama University, 2024)
The study aimed to test the impact of company size, growth, profitability, tangible assets and financial leverage on financial reporting quality. To achieve that goal; Secondary data was collected from the annual financial reports of six insurance companies listed on the Damascus Exchange Securities, and the study covered an 11-year period from 2010 to 2020. The study used cross-sectional data, and it was analyzed based on the E-views 10 program. The results showed that company size and profitability have a positive impact on financial reporting quality, which means that companies with large size and profitability are less inclined to practice earning management. financial leverage impact was negative and companies have to reduce its levels, but growth and tangible assets, were not statistically significant, so they didn’t affect financial reporting quality